Effect of p300 HAT Activity on Myogenic Differentiation - Hamed, Munerah (Université d'Ottawa / University of Ottawa, 2013)
Skeletal muscle specification and differentiation programs are regulated by the myogenic regulatory factors which include Myf5, MyoD, myogenin and Mrf4. Upstream of the MRFs, the transcription co-activators and other intracellular and extracellular signals play crucial roles in regulating skeletal myogenesis. Histone acetyltransferase activity of p300 is required for Myf5 and MyoD expression. Furthermore, the MyoD core enhancer region is indispensable for MyoD expression. However, the mechanism by which p300 activates MyoD gene expression is to be determined. The histone acetyltransferase activity of p300 can be inhibited by small molecule inhibitors such as curcumin. Thus, using the inhibitor approach on stem cells is useful to investigate the role of p300 in activating MyoD expression during myogenesis. We here show that curcumin was able to inhibit stem cell determination and differentiation into skeletal myocytes. We also show that p300 is present, and histone acetylation is high at the core enhancer region. Therefore, we provide evidence that p300 is directly involved in MyoD gene expression during skeletal myogenesis.
Keywords: p300; myod; histone acetylation